A Survey on Congestion Control Techniques for Ad Hoc Routing Protocol in VANET - Mangal, Priyanka; Sariya, Amit Kumar (International Journal of Computer Sciences and Engineering, 2020)
A Vehicular Ad-Hoc Network uses moving cars as nodes to create a mobile network. VANET turns every participating car into a wireless router and allow cars to connect and create a wide range network. VANETs are developed for increasing the driving safety and comfort of automotive end users. It can provide wide variety of services such as Intelligent Transportation System (ITS) e.g. safety applications. Many of safety applications built in VANETs are required real-time communication with high reliability. The main issues are to avoid deterioration of communication channels in dense traffic network. VANET protocols have to face high challenges due to dynamically changing topologies. Many of studies suggested that suitable congestion control algorithms are required to provide efficient operation of a network. However, all congestion control algorithms are not applicable to event-driven safety messages. This paper discusses various existing congestion control algorithms in different congested scenarios. The effectiveness of congestion control algorithm is evaluated through the simulations using Network Simulator-2 (NS2).